Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios Predict All-Cause Mortality in Acute Pulmonary Embolism - Phan, Trung; Brailovsky, Yevgeniy; Fareed, Jawed; Hoppensteadt, Debra; Iqbal, Omer; Darki, Amir (Clinical and applied thrombosis/hemostasis, 2020)
The aim of this study was to investigate the utility of the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) to predict all-cause mortality in patients presenting with acute pulmonary embolism (PE). Three hundred consecutive patients with acute PE between March 2016 and December 2018 were retrospectively analyzed. We identified 191 patients who met the study inclusion criteria. Twenty-eight patients died during the study period. There was a significant difference in PLR, but not NLR, between patients with low risk, submassive, and massive risk PE (P = .02 and P = .58, respectively, by the Kruskal-Wallis test). Elevated NLR and PLR were associated with all-cause mortality (P < .01 and P < .01, respectively). Neutrophil-to-lymphocyte ratio of 5.46 was associated with all-cause mortality with sensitivity of 75.0% and specificity of 66.9% (area under the curve [AUC]: 0.692 [95% confidence interval, CI]: 0.568-0.816); P < .01). Platelet-to-lymphocyte ratio of 256.6 was associated with all-cause mortality with sensitivity of 53.6% and specificity of 82.2% (AUC: 0.693 [95% CI: 0.580-0.805]; P < .01). Neutrophil-to-lymphocyte ratio and PLR are simple biomarkers that are readily available from routine laboratory values and may be useful components of PE risk prediction models.